2016
DOI: 10.1111/pim.12326
|View full text |Cite
|
Sign up to set email alerts
|

Fasciola hepatica infection reduces Mycobacterium bovis burden and mycobacterial uptake and suppresses the pro‐inflammatory response

Abstract: SUMMARYBovine tuberculosis (BTB), caused by Mycobacterium bovis, has an annual incidence in cattle of 0.5% in the Republic of Ireland and 4.7% in the UK, despite long-standing eradication programmes being in place. Failure to achieve complete eradication is multifactorial, but the limitations of diagnostic tests are significant complicating factors. Previously, we have demonstrated that Fasciola hepatica infection, highly prevalent in these areas, induced reduced sensitivity of the standard diagnostic tests fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 76 publications
2
37
1
Order By: Relevance
“…It was interpreted to mean that fluke co‐infection could drive the false positive rate, however, given the potential for fluke to impact on the pathogenesis of bTB (e.g. by being associated with smaller size or counts of lesions, Byrne, Graham, Brown, et al, or reduced bacterial load Garza‐Cuartero et al, ), it is possible that, if anything, liver fluke infection could reduce the bTB‐VL confirmation rates of truly infected cattle. Other research from Northern Ireland on the impact of liver fluke status on SICCT tuberculin reaction sizes uncovered a negative association at univariable level, but this association was confounded by age‐class (Byrne et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was interpreted to mean that fluke co‐infection could drive the false positive rate, however, given the potential for fluke to impact on the pathogenesis of bTB (e.g. by being associated with smaller size or counts of lesions, Byrne, Graham, Brown, et al, or reduced bacterial load Garza‐Cuartero et al, ), it is possible that, if anything, liver fluke infection could reduce the bTB‐VL confirmation rates of truly infected cattle. Other research from Northern Ireland on the impact of liver fluke status on SICCT tuberculin reaction sizes uncovered a negative association at univariable level, but this association was confounded by age‐class (Byrne et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental infection studies indicate that co‐infection in this system can lead to reduced immunological response during bTB diagnostic skin tests (based on reaction the tuberculin Purified Protein Derivative [PPD]), potentially reducing the efficacy of bTB control programs (Flynn, Mannion, Golden, Hacariz, & Mulcahy, ; Flynn et al, ). Recent experimental research has indicated that co‐infected animals may harbour lower M. bovis burdens, suggesting a potential role for therapeutic effects of co‐infection or the drive towards a latent stage of bTB infection (Garza‐Cuartero et al, ). There has been some evidence presented that suggest that such interaction can have an impact at the herd level also.…”
Section: Introductionmentioning
confidence: 99%
“…These results could indicate that co-infection with liver fluke may affect the pathogenesis or progression of infection. Recently, Garza-Cuartero et al (2016) found that experimentally co-infected animals had lower M. bovis burdens (measured in bacterial load) in comparison with animals that were not infected with liver fluke. Furthermore, the authors report both reduced uptake and recovery of M. bovis from tissues from co-infected animals.…”
Section: Liver-fluke and Btb Riskmentioning
confidence: 99%
“…Furthermore, the authors report both reduced uptake and recovery of M. bovis from tissues from co-infected animals. Garza-Cuartero et al (2016) propose, based on their data, that co-infection with liver fluke could "limit the uptake of mycobacteria, setting the stage for a slower rate of bacterial proliferation and lesion development, leading to a reduced proinflammatory response". It should be noted, however, that the results of the association between liver fluke infection and infection at routine slaughter were marginal (e.g., LRS Odds-Ratio: 0.87; 95% CI: 0.76-1.00; p = 0.042) in the present study.…”
Section: Liver-fluke and Btb Riskmentioning
confidence: 99%
“…Interestingly, in the experimental work undertaken by Flynn, Mannion, Golden, Hacariz, and Mulcahy (), there were lower numbers of animals with lesions and lower lesion scores disclosed in co‐infected animals (3/6 with lesions; mean lesion score: 2.7) in comparison with M. bovis‐ infected cattle alone (5/6 with lesions; mean lesion score: 4.2). Other recent experimental research has found that co‐infected animals ( n = 12) had a non‐significantly lower number of infected tissues and that there were no differences in the number of lesions or their distribution relative to M. bovis only infected cattle (Garza‐Cuartero et al., ). Furthermore, less M. bovis was recovered in co‐infected animals; this suggested a lower bacterial burden in co‐infected animals (Garza‐Cuartero et al., ; Lucena et al.…”
Section: Discussionmentioning
confidence: 83%